Bio-concrete on chloride condition: effect on compressive strength and water penetration - Teddy, T.; J.M., Irwan; Othman, N.; Gani, P. (Construction Research Institute of Malaysia (CREAM), 2018)
In recent years, the beneficial effect of sulphate reduction bacteria (SRB) to induce calcium carbonate precipitation on the concrete structure has gradually increase great attention in the industry. In this study, different SRB concentration (0%, 3%, 5% and 7%) and water cement ratio (0.4w/c, 0.5w/c and 0.6w/c) was investigated in term of compressive strength and water penetration. Since the sample curing in saline water, thus, the sample on chloride condition also investigated accordingly. Compressive strength and water penetration test were performed at the stage of 28th, 56th, 90th, 180th and 360th day of curing period. Test results indicated that the best SRB concentration to be mixed in bio-concrete was 5% while 0.5w/c for water cement ratio. Both values enhanced significantly the compressive strength and reduced porosity and water penetration of bio-concrete. The maximum increased of compressive strength in 0.5w/c is 58.6MPa was observed with 5% of SRB on the day 180 of curing time. Meanwhile, the lowest water penetration was recorded on the last day (day 360) of curing with 2.93cm at the 5% and 0.6w/c of SRB concentration and water cement ratio, respectively. These improvements were due to deposition on the SRB cells within the pore of the concrete cube as cured in chloride water. Results of this study demonstrated the role of SRB induced calcium carbonate precipitation in improving the concrete structure cured in extreme condition in term of compressive strength and water penetration.